Baked eggs: catastrophic heatwave‐induced reproductive failure in the desert‐adapted Zebra Finch (Taeniopygia guttata). (26th April 2021) - McCowan, Luke S. C.; Griffith, Simon C.
Abstract : Animals living in arid or semi‐arid environments are frequently exposed to the challenge of dealing with extreme high ambient temperatures that are predicted to become more severe with a changing climate as heatwaves increase in frequency and severity. In addition to the adverse effects of heatwaves on adults, high temperatures are likely to have detrimental effects on breeding success. During incubation, parents need to regulate the temperature of their clutch within the optimal range for development and below levels that can lead to adverse effects on development or lethal outcomes. We report on the effects of a heatwave on a bout of summer breeding in a monitored population of wild Zebra Finches. One extended heatwave resulted in the complete mortality of 23 of 25 (95%) clutches laid before or during this event, with embryo mortality confirmed with the application of a heart rate monitor (98 of 100 eggs). We found that no embryo survived a cumulative exposure of 20 h or more at 40.5 °C during the incubation period. However, some embryos survived higher temperatures for shorter periods. Our findings demonstrate the catastrophic effects of heatwaves on avian reproduction, even in a species that is well adapted to a hot and unpredictable environment.